2018
DOI: 10.1186/s40425-018-0425-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns, predictors and subsequent outcomes of disease progression in metastatic renal cell carcinoma patients treated with nivolumab

Abstract: BackgroundNivolumab is approved for the treatment of refractory metastatic renal cell carcinoma. Patterns and predictors of progressive disease (PD) on nivolumab, and outcomes in such patients are lacking.MethodsA retrospective analysis of patients (pts) with metastatic clear cell renal cell carcinoma (ccRCC) who received nivolumab at Cleveland Clinic (2015–2017) was performed. PD was defined per Response Evaluation Criteria in Solid Tumors (RECIST) v1.1 or clinical progression as per treating physician. Univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
46
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 33 publications
4
46
0
Order By: Relevance
“…In our case series, the brain was the most common metastatic organ in patients with new lesion appearance, supporting the finding of the previous study . In contrast, the incidence of new BMs has ranged from 3 to 9.7% in targeted therapy .…”
supporting
confidence: 91%
See 1 more Smart Citation
“…In our case series, the brain was the most common metastatic organ in patients with new lesion appearance, supporting the finding of the previous study . In contrast, the incidence of new BMs has ranged from 3 to 9.7% in targeted therapy .…”
supporting
confidence: 91%
“…Recently, a remarkably high incidence of new BMs during nivolumab therapy for mRCC was reported . In that study, the brain was the most common metastatic organ in patients with new lesion appearance during nivolumab therapy (8/23, 35%), suggesting that the pattern of PD might be different in nivolumab from that in molecular‐targeted therapy.…”
mentioning
confidence: 98%
“…Although there are few reports of prognostic factors for mRCC treated with ICIs, several studies have shown the association of some inflammatory markers with the prognosis of patients with various malignant diseases treated with ICIs (Table 3). [97][98][99][100][101][102][103][104][105][106] These reports indicate that the parameters related to inflammation might also have some prognostic impact on patients with mRCC treated with ICIs. Further study is expected to clarify the link between the mechanism of inflammation and the effects of ICIs, and to identify the markers related to inflammation to predict or evaluate the effects of ICIs.…”
Section: Inflammatory Markersmentioning
confidence: 87%
“…Although there are few reports of prognostic factors for mRCC treated with ICIs, several studies have shown the association of some inflammatory markers with the prognosis of patients with various malignant diseases treated with ICIs (Table ) . These reports indicate that the parameters related to inflammation might also have some prognostic impact on patients with mRCC treated with ICIs.…”
Section: Biomarkers For Immune Checkpoint Therapymentioning
confidence: 99%
“…The potential cause of these differences remains unclear, the determination and the best cut-off values of neutrophil, lymphocyte and hemoglobin should enroll in further randomized controlled trials to con rm their relevance in the incidence of BM and prognosis, which may help build a easy-to-calculate laboratory score for BM from NSCLC. Additionally, previous reports indicated that the serum markers such as peripheral blood cell counts can be used as a predictor for response to immunotherapy (31). Therefore, the in-depth study about prognostic values of neutrophil, lymphocyte and hemoglobin will help us to further understand the immune mechanism of NSCLC BM, and ultimately help us to make better clinical decisions in circumstances such as facing moderate-tosevere irAEs and distinguishing tumor ares (or pseudoprogressions) from true progressions.…”
Section: Discussionmentioning
confidence: 99%